Influencing Factors of Job Satisfaction in TechnicalOrganization - Ibrahim, Muhammad; ., Nadir Khan; ., Yasser Khan; ., Zahid Mahmood Awan; ., Muhammad Khalil Shahid, Abdul Kareem (Journal of Economics and Behavioral Studies, 2012)
The aim of this research is to find out the core factors, which have a strong impact on Job Satisfaction in Technical Organizations in Pakistan. This study discusses the main variableslike Effective Recruitment, Rewards, and Personality of employees and Role of Leadership and their effect on job satisfaction. First hand, data was used in the research and some important recommendations were made for the improvement of Job Satisfaction of employees working at Ufone. It is expected that this study will make comprehensive note to the environment of Ufone especially and every other organization in general, how to make their working environment acceptable to the employees.